2007
DOI: 10.1073/pnas.0707348104
|View full text |Cite
|
Sign up to set email alerts
|

Intensive training in adults refines A1 representations degraded in an early postnatal critical period

Abstract: The spectral, temporal, and intensive selectivity of neurons in the adult primary auditory cortex (A1) is easily degraded in early postnatal life by raising rat pups in the presence of pulsed noise. The nonselective frequency tuning recorded in these rats substantially endures into adulthood. Here we demonstrate that perceptual training applied in these developmentally degraded postcritical-period rats results in the recovery of normal representational fidelity. By using a modified go/no-go training strategy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 51 publications
(79 reference statements)
10
51
0
Order By: Relevance
“…Consistent with earlier studies (11,12), we showed that early PN exposure significantly increased the tonotopic index (degraded tonotopicity) of A1 and broadened frequency tuning (i.e., BW20) of A1 neurons. We further showed that the normalized response rates for PN-exposed rats were lower at high stimulus repetition rates (i.e., Ͼ7 pps) than in naïve rats, indicating decreased cortical responses to high-rate stimuli after noise exposure.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with earlier studies (11,12), we showed that early PN exposure significantly increased the tonotopic index (degraded tonotopicity) of A1 and broadened frequency tuning (i.e., BW20) of A1 neurons. We further showed that the normalized response rates for PN-exposed rats were lower at high stimulus repetition rates (i.e., Ͼ7 pps) than in naïve rats, indicating decreased cortical responses to high-rate stimuli after noise exposure.…”
Section: Discussionsupporting
confidence: 80%
“…By contrast, previous studies that applied continuous noise exposure during the critical period reported that noise-rearing did not necessarily permanently impair cortical temporal processing into adulthood; the cortex returned to ''normal'' after animals were returned to a normal acoustic environment (13,14). A similar difference in the duration of exposure-induced plasticity has been reported in spectral domain development of A1 when rats were exposed to pulsed (11,12) or continuous (13) noise during the critical-period epoch. It has been proposed that PN-rearing prematurely advances the timing of critical-period closure for cortical plasticity, whereas continuous noise rearing, in contrast, results in the delay of criticalperiod closure.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Consistent with earlier studies (6,7), the frequency representation of A1 determined using a conventional mapping procedure was complete and orderly in control rats, with isofrequency representational bands oriented approximately orthogonal to an orderly sound frequency representational (tonotopic) gradient ( Fig. 2 Top Left).…”
Section: Resultssupporting
confidence: 71%